Evaluation of High School Curriculum in Central Java - Yuli Utanto, Luluk Elyana, Sudaryanta, Yoris Adi Maretta (International Journal of Advanced Science and Technology, 2020)
This study evaluates the competence of high school (SMA) teachers in implementing the 2013 curriculum including aspects: KTSP documents, RPP documents, learning process and learning assessment. The evaluation was carried out for high school teachers who became Model Schools and Impact Schools in all Regencies/Cities in Central Java Province on a scale of 0-5. The results show the acquisition of various values. Evaluation of Education Unit Level Curriculum documents (KTSP) shows varieties of quantitative values. The lowest score obtained was 2.76 (Wonogiri Regency), while the highest achievement score was 3.95 (Jepara Regency and Klaten Regency). The average KTSP document obtained as an achievement in Central Java Province is 3.50. The evaluation of the Learning Implementation Plan (RPP) document shows a varied quantitative value. The lowest score obtained was 3.06 (Boyolali Regency), while the highest score was 3.97 (Jepara Regency). The average value of Syllabus documents and RPP obtained as achievements of Central Java Province is 3.69. Evaluation of the learning process shows quantitative values vary. The lowest score obtained was 2.52 (Pekalongan), while the highest score was 3.99 (Grobogan Regency). The average value of the Learning Process obtained as an achievement of Central Java Province is 3.57. Evaluation of learning assessment results shows varying levels of achievement. The lowest value obtained was 2.75 (Boyolali Regency), while the highest achievement value was 4.00 (Jepara Regency). The average value of the learning assessment obtained as an achievement in Central Java Province is 3.55. The competence of high school teachers in Central Java in implementing the 2013 curriculum still requires assistance and guidance so that competence increases. Keywords: Curriculum evaluation, High school level, Central Java Province